2022
DOI: 10.1186/s12866-022-02679-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of population structure, antimicrobial resistance, virulence factors, and morphology of methicillin-resistant Macrococcus caseolyticus in global clades

Abstract: Macrococcus caseolyticus is an opportunistic pathogen that is frequently isolated from dairy products and veterinary infections. Recent studies have reported the possibility of methicillin resistance that be transferred among staphylococcal species in foods. The present study examined the population structure, antimicrobial resistance, virulence factors, and morphology of methicillin-resistant M. caseolyticus by investigation of 94 genomes derived from both isolates in beef (n = 7) and pork (n = 2) at Shanghai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Future efforts to find the mature RiPP will also focus on Streptococcus oralis , an additional species that was sequenced and shown to possess the grc gene cluster after the initial generation of our RaS-RiPP network. Macrococcus caseolyticus , an opportunistic pathogen isolated from dairy products, offers an alternative strain as it encodes a homologous grc cluster on a plasmid, albeit with a different precursor peptide sequence . These strains further underline the complex secondary metabolites that are encoded in underexplored microbes, notably those with small genomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future efforts to find the mature RiPP will also focus on Streptococcus oralis , an additional species that was sequenced and shown to possess the grc gene cluster after the initial generation of our RaS-RiPP network. Macrococcus caseolyticus , an opportunistic pathogen isolated from dairy products, offers an alternative strain as it encodes a homologous grc cluster on a plasmid, albeit with a different precursor peptide sequence . These strains further underline the complex secondary metabolites that are encoded in underexplored microbes, notably those with small genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Macrococcus caseolyticus, an opportunistic pathogen isolated from dairy products, offers an alternative strain as it encodes a homologous grc cluster on a plasmid, albeit with a different precursor peptide sequence. 81 These strains further underline the complex secondary metabolites that are encoded in underexplored microbes, notably those with small genomes.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Comparatively, some genomic elements identified here were present across multiple Macrococcus spp., indicating shared inter-species functional potential for some phenotypes. Methicillin resistance genes mecB and mecD , for example, were variably present within multiple Macrococcus species (via GTDB-Tk; Figure 3), mirroring previous studies, which have reported mecB and/or mecD in various Macrococcus spp., including M. caseolyticus (Schwendener et al, 2017; MacFadyen et al, 2018; Zhang et al, 2022), M. bohemicus (Foster and Paterson, 2020), M. canis (Chanchaithong et al, 2019), and M. goetzii (Maslanova et al, 2018). Outside of the AMR space, we further identified proteins that shared homology with virulence factors in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Aureolysin is an extracellular zinc-dependent metalloprotease secreted by Staphylococcus aureus , which plays a crucial role in host immune system evasion (Thammavongsa et al, 2015; Pietrocola et al, 2017). While others have detected aureolysin homologues in Macrococcus genomes (Mazhar et al, 2019a; b; Zhang et al, 2022), the roles this protein plays in Macrococcus interactions with human or animal hosts (if any) are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation